Reimagining Christian Hope(lessness) in the Anthropocene - Robinson, Timothy (Religions, 2020)
Faith in the Anthropocene requires a re-imagined account of Christian hope. Research on the emergence of eco-anxiety disorder shows that climate crisis and ecological destruction have psychological and emotional effects on persons and communities, producing fear, despair, and hopelessness. Accounts of hope in recent environmental literature and in traditional Christian formulations rely on faith in political will, technological innovation, or an omnipotent divine sovereign to intervene and save. Such accounts are inadequate for this moment. A re-imagined notion of Christian hope will embrace hopelessness, understood as the relinquishment of false optimism that the climate crisis can be reversed and a commitment to act without expectation of success, but with a commitment to nurturing the wisdom to live more humanly.